Pediatric Secondary Overtriage in a Statewide Trauma System. Issue 9 (September 2016) - Leung, Alexander; Bonasso, Patrick; Lynch, Kevin; Long, Dustin; Vaughan, Richard; Wilson, Alison; Con, Jorge
Secondary overtriage is a term that describes patients who are discharged home shortly after being transferred, an indication that transfer and hospitalization were unnecessary. The study goal was to identify factors associated with secondary triage. A statewide trauma registry was used to identify trauma patients aged less than 18 years during a 6-year period (2007–2012) who were discharged within 48 hours from arrival and did not undergo a surgical procedure. We compared those that were treated at initial facility and those transferred to a second facility using clinical indices including patterns of injury pattern using multivariate logistic regression. Of the 4441 patients who fit our inclusion criteria, 801 (18%) were transferred. Younger age groups were more likely to be transferred. Factors associated with being transferred included head, spinal, and facial injuries, and patient arrival during the nighttime work shifts. In conclusion, young patients who have signs of possible neurological or spinal injuries and those who arrive during nondaytime shifts during the workday are more likely to be transferred to another trauma center. These may reflect the comfort level and resources of the local facility.